Efektivitas Pelatihan Keterampilan Kerja Dalam Meningkatkan Daya Saing Tenaga Kerja: (Studi Kasus Di BLK Kota Padangsidimpuan ) - Anisah Nasution; Mawaddah Irham (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research discusses the effectiveness of occupational skills training in improving labor competitiveness. The purpose of this study is to analyze the impact of vocational skills training on improving the ability and competence of the workforce in facing competition in an increasingly competitive job market. The research method used is a literature study and secondary data analysis related to the vocational skills training program and the results of improving the competitiveness of the workforce. The results show that vocational skills training is effective in improving workforce competencies, including increased productivity, adaptability and innovation in a diverse work environment. With the right training in place, the workforce has a better chance of accessing quality jobs and making a positive contribution to economic development. However, factors such as relevant training curriculum, interactive teaching methods and post-training monitoring are also important in determining the success of vocational skills training. In conclusion, vocational skills training has a significant role to play in improving the competitiveness of the workforce, with the potential to have a positive impact on economic growth and social development.